KONSEP KEPERAWANAN TERHADAP PEMBATALAN PERKAWINAN TIJAUAN HUKUM ISLAM DAN FEMINISME - Nada Putri Rohana; Mustafid Mustafid (Indonesian Journal of Shariah and Justice, 2021)
Virginity in fact has a variety of concepts, namely in Indonesia the concept of female virginity is that the blood membrane or hymen is still intact or a virgin concept in the presence of virgin blood. The concept is considered urgent in marriage so that it causes harassment which can disrupt the integrity and harmony of the household. The concept of virginity can be a syiqaq (disputes / disputes) so that stigma arises as reasons for canceling marriages. Regarding the cancellation of vulnerable marriages related to this issue is associated with KHI Article 72 paragraph (2), then about thereasons or reasons for divorce in KHI Article 116 letter f. This research shows that the concept of virginity undergoes a complex and sensitive evolution of law in social, cultural and religious life even in the household. The concept of virginity towards the annulment of marriage in the perspective of Islamic law and feminism presents causation, namely: (hifdz al-din) nurturing religion (by rectifying intentions in marriage and adding faith in oneself and soul to earnest in the purpose of marriage), (hifdz al-nafs ) nurturing oneself (the prohibition of approaching adultery,and the necessity of guarding the genitals and the view and prohibition of insulting the partner with allegations of dzolim), (hifdz al-nas / irdl) maintaining offspring and honor (by guarding and understanding the rules in marriage related to rights and obligations), (hifdz al-mal) preserves property (that the woman is jewelry, is clothing for the husband, vice versa, is the field for the husband, is the property and honor of the husband so that it must be safeguarded by disgrace), and (hifdz al -'aql) maintains the mind (the necessity to study as a means for men or women to open their mindset in understanding the life of the pern ikahan is a matter of sexual relations, needs healthy sexual education in order to avoid stigma or suspicion or anxiety that disrupts domestic life). Thus, it can control people's lives in accordance with the legal concept in order to rectify stigma speculation.